PREVALENCE OF GASTRIC PRECANCEROUS CONDITIONS : A SYSTEMATIC REVIEW - Prameswari, Pretika; Azhari, Ririn (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Gastric carcinoma is a common malignant disease associated with an unfavorable prognosis in the case of late dia-gnosis. The most significant precancerous condition is chronic atrophic gastritis and intestinal metaplasia caused by Helicobacter pylori infection. These longlasting changes may lead to formation of dysplastic precancerous lesions. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 1.045 articles, whereas the results of our search on SagePub brought up 701 articles. The results of the search conducted for the last year of 2013 yielded a total 12 articles for PubMed and 8 articles for SagePub. In the end, we compiled a total of 4 papers, 3 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: Precancerous conditions including chronic atrophic gastritis gastritis, metaplasia, foveolar hyperplasia and gastric hyperplastic polyps derived from the gastric epithelium have been concluded, based on the overview of gastric epithelial histological organization and its renewal.